Writing an editorial - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
An editorial may be written by the editor or someone invited by the editor. It serves many other purposes, including critiques of original articles published in the same issue of the journal, concise reviews of topics that do not warrant a full-length invited review, and other topics on very recent developments that are deemed by the editor to be important to readers of the journal and the community. As there is typically a limited space in which to deliver its contents, the message contained in the editorial needs to be well thought out and concisely delivered. It should contain the correct sequence of the elements of critical argument, ideally supported by evidence, and end with a clear conclusion.